2016
DOI: 10.1016/j.ijom.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of three-dimensional visualization in mobile apps for patient education regarding orthognathic surgery

Abstract: Abstract'Sur-face', is an interactive mobile app illustrating different orthognathic surgeries and their potential complications. This study aimed to evaluate the efficacy of Sur-face by comparing two methods of delivering patients' information regarding orthognathic surgeries and their related potential complications: a mobile app with interactive 3D animations and a voice recording containing verbal instructions only. For each method, the participants' acquired knowledge was assessed using a custom designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
(18 reference statements)
1
7
0
1
Order By: Relevance
“…Also, to the best of our knowledge, there are no studies in medical students that links smartphone addiction, psychological distress, and neurotic traits. Medical students use smartphones to facilitate retrieving information resources [ 32 34 ]. There is almost universal ownership of smartphones among medical students [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, to the best of our knowledge, there are no studies in medical students that links smartphone addiction, psychological distress, and neurotic traits. Medical students use smartphones to facilitate retrieving information resources [ 32 34 ]. There is almost universal ownership of smartphones among medical students [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…These devices can provide learners with easy access to a wide variety of educational resources to support learning in the clinical environment. Mobile devices are used by medical students to facilitate access to a wide range of resources including anatomy, drug information, clinical scoring systems and eBooks (Electronic Books) [ 4 6 ] with higher levels of use of devices by students in the clinical years [ 7 ]. However, for mLearning to be successfully integrated into medical education strategies and practices, institutions, clinicians and students must understand their potential, impacts and limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Information and communication technology has proved to be a critical component of teaching and Therefore, in view of the technological scenario that we are experiencing, mobile devices are seen as a great strategy to contribute to health education (Farias et al, 2015;Khatoon, Hill, & Walmsley, 2015). Moreover, the articles that discussed the use of applications in relation to Patient Orientation concluded that the applications represent an important vehicle for information access (Pulijala et al, 2016) for selfcare in oral health (Petruzzi & Benedittis, 2016;Li et al, 2016, Zotti et al, 2016. Thus, the use of applications can contribute to an upstream approach to oral health promotion, that is, it could minimize inequalities, facilitate access to information relevant to health and the creation of favorable environments for it.…”
Section: Discussionmentioning
confidence: 99%